Fault localisation for WS-BPEL programs based on predicate switching and program slicing - Sun, Chang-ai; Ran, Yufeng; Zheng, Caiyun; Liu, Huai; Towey, Dave; Zhang, Xiangyu (Elsevier, 2018)
Service-Oriented Architecture (SOA) enables the coordination of multiple loosely coupled services. This allows users to choose any service provided by the SOA without knowing implementation details, thus making coding easier and more flexible. Web services are basic units of SOA. However, the functionality of a single Web service is limited, and usually cannot completely satisfy the actual demand. Hence, it is necessary to coordinate multiple independent Web services to achieve complex business processes. Business Process Execution Language for Web Services (WS-BPEL) makes the coordination possible, by helping the integration of multiple Web services and providing an interface for users to invoke. When coordinating these services, however, illegal or faulty operations may be encountered, but current tools are not yet powerful enough to support the localisation and removal of these problems. In this paper, we propose a fault localisation technique for WS-BPEL programs based on predicate switching and program slicing, allowing developers to more precisely locate the suspicious faulty code. Case studies were conducted to investigate the effectiveness of the proposed technique, which was compared with predicate switching only, slicing only, and one existing fault localisation technique, namely Tarantula. The experimental results show that the proposed technique has a higher fault localisation effectiveness and precision than the baseline techniques.